MOTIVASI MAHASISWA KEPERAWATAN UNIVERSITAS PELITA HARAPAN TENTANG KEPUTUSAN MENJADI SUKARELAWAN COVID-19 - Grace Solely Houghty; Ballsy C. A. Pangkey; Marianna Rebecca Gadis Tompunu (Jurnal Keperawatan Priority, 2022)
The Ministry of Education and Culture (Kementerian Pendidikan dan Kebudayaan) invites final year students in health faculties to volunteer during the Covid-19 pandemic. The number of students in the nursing study program was 1084, and those who registered as volunteers were 174 (16.5%). As a humanitarian professional nurse, there should be many nursing students who have the motivation to volunteer and decide to volunteer. Based on this phenomenon, the researcher is interested in identifying student motivation regarding volunteering at the Pelita Harapan University Nursing Study Program. The research design used a cross-sectional survey research design. The instrument used was a functional model questionnaire from Clary translated by the back-translation method and tested for validity and reliability. The population was 174 nursing study program students who are volunteers. This sampling type is a total sampling of 137 students participating in the study with a response rate of 78.7%. The results showed that the motivation of students for volunteering is high. The highest motivation is in the protective component 78 people (56.93%). The majority of students stated that the motivation of the protective functional model, values, career (carrier), social (social), understanding (understanding), and improvement (enhancement) is in the very important range, very important, and important.